Analyzing Nematic to Isotropic (N-I) Phase Transition of nCB Liquid Crystals Using Logger Pro - Seide, Medaelle; Doran, Mathew C.; Sharma, Dipti (European Journal of Applied Sciences, 2022)
This paper reports detailed analysis of Nematic to Isotropic (N-I) phase transition of n-Cyanobiphenyl (nCB) Liquid Crystals (LC) using Logger Pro. Three bulk samples of nCB liquid crystal family, 4-Pentyl-4’-cyanobiphenyl (5CB), 4-Hexyl-4’-cyanobiphenyl (6CB), and 4-Heptyl-4’-cyanobiphenyl (7CB) were processed through the Differential Scanning Calorimetry (DSC) instrument for heating and cooling scans. The DSC data is then analyzed using Logger Pro. Logger Pro is a data analysis tool used to collect and analyze data in educational institutes. Our interest is to use Logger Pro in the research area to analyze DSC data of these LCs to get detailed results of N-I phase transition. Logger pro has been proven to be a good data analysis tool to find results in detail for these LCs in this paper. It is found that as nCB gets heavier and its C-C tail gets larger, the N-I phase transition shifts towards higher temperature in heating and shows an increase in enthalpy, wings jump, molecular mobility and molecular disorder.